Migrating cells control morphogenesis of substratum serving as track to promote directional movement of the collective. - Macabenta, F.; Stathopoulos, A. (Development, 2019)
In Drosophila embryos, caudal visceral mesoderm (CVM) cells undergo bilateral migration along the trunk visceral mesoderm (TVM) in order to form midgut muscles. Mutation of FGF receptor Heartless (Htl) has been shown to cause CVM migration defects, particularly midline crossing of the bilateral groups. Here, we show that htl mutants also exhibit TVM defects including contralateral merging. Both CVM mismigration and TVM contralateral merging are attenuated by restoring FGF signaling specifically in the CVM, suggesting that migrating CVM cells influence TVM morphogenesis; however, the inverse, supplying FGF to the TVM, does not rescue CVM mismigration. In addition, we show that FGF regulates integrin expression in both tissues, but only providing a source of integrin specifically to the TVM attenuates the contralateral merging phenotype. Finally, we demonstrate that the CVM influences cell shape in the TVM, and a loss of CVM results in TVM morphological defects. In summary, this study provides insight into how a migrating collective of cells can influence their tissue substrate and supports the view that morphogenesis of tissues during development is interdependent.